ERA-40 Monthly Means of Surface and Flux Fields - European Centre For Medium-Range Weather Forecasts (UCAR/NCAR - Research Data Archive, 2004)
The monthly means of surface and flux fields from ECMWF ERA-40 reanalysis project are in this dataset.